Measurement and Convergence Test of Green Economic Efficiency of the Yangtze River Economic Belt Under Different Spatial Network Correlation - Liu, Shuguang; Song, Lei; Huang, Yue (Frontiers in Environmental Science, 2022)
The green and coordinated development of the Yangtze River Economic Belt (YREB) is of great significance to the overall high-quality growth of the Chinese economy. Targeting green development issues and regional disparities in the YREB, this paper proposes a method that combines the Super-EBM and Malmquist–Luenberger indexes to measure the green economic efficiency (GEE) of 108 cities from 2003 to 2018. Moreover, we adopted the dynamic Spatial Dubin Panel model to conduct a convergence test including economic linkage, capital liquidity, talent mobility, and information sharing. The outcomes pointed out that: (1) the green economy shows a volatile growing trend, and technological progress is the main source of YREB’s GEE; (2) we have noticed the formation of spatial differentiation in the three basins, especially in central areas of big cities such as Shanghai, Hangzhou, Wuhan, and Chongqing; (3) the GEE follows a global β convergence trend that narrows the gap in green economic efficiency. More specifically, the downstream (11.48%) has the fastest convergence rate, followed by the midstream (8.09%) and upstream (7.97%); (4) capital liquidity, governance, and economic openness contribute a lot to maintaining the convergence trend. The primary contributions of this study are the policy recommendations to promote green development and narrow the gap in the YREB to ultimately achieve effective coordinated development.